(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
نفذ هذا العمل للاستفادة من كمبوست فضلات انتاج الفطر الزراعي في زراعة محصول استراتيجي هام وهو البطاطا. حيث يتم تقييم أثر استخدام هذا الكمبوست في محتوى أوراق البطاطا من عناصر الـ (NPK) ونوعية الدرنات المنتجة من ناحية محتواها من النشاء والمادة الجافة والرماد والبوتاسيوم. حيث أن استخدام هذه الفضلات في الزراعة يقلل من تكاليف الانتاج والآثار السلبية المحتملة على البيئة من خلال الحد من الاستخدام المفرط للأسمدة والمبيدات الزراعية التي تستخدم عادة في الطرق التقليدية لإنتاج البطاطا، والتي تعتبر مصدرا رئيسا لتلوث المجاري المائية والمياه الجوفية. تم تصميم التجربة على اساس القطاعات العشوائية الكاملة بثلاثة مكررات، وإضافة بقايا كمبوست انتاج الفطر الزراعي للمساكب قبل زراعتها بمحصول البطاطا (صنف سبونتا) بشكل متدرج وبمستويات متزايدة (100-75-50-25-0) %، لمقارنتها مع معاملة التسميد المثالي التي تتكون من خليط من الأسمدة الكيميائية والعضوية مع التربة تم تحديد تأثير المعاملات المختلفة في تراكيز عناصر(NPK) في الأوراق وكذلك تراكيز البوتاسيوم والنشاء والرماد والمادة الجافة في الدرنات، حيث أظهرت النتائج زيادة تراكيز (NPK) في الأوراق مع زيادة مستويات بقايا كمبوست الفطر في وسط النمو. وزيادة نسبة النشاء والمادة الجافة والبوتاسيوم في الدرنات في حين انخفضت نسبة الرماد فيها. This work was Carried out to take an advantage of the spent mushroom compost in production of potato crop as one of the important agricultural cultivated and strategic crops in order to evaluate the impact of the use of this compost on potato leaf content of NPK elements, the quality of produced tubers and their contents of starch, dry matter, ash and K. Where the use of the spent mushroom compost in agriculture reduces cost of production and the potential negative effects on the environment through the reduction of the excessive use of mineral fertilizers and agricultural pesticides which are commonly used in the traditional methods for the production of potatoes, and considered as a major source for streams and groundwater pollution. The split plot randomized design was followed in this experiment in three replicates, by the application of the spent mushroom compost in the cultivation of potato crop (var. Spunta) in an increasing gradual rates (0, 25, 50, 75, 100%) in the bedding medium, to be compared with soil and organic manure mixed with chemical fertilizers as an ideal treatment. (NPK) concentrations in the plant leaves and the tubers contents of starch, K, ash and dry matter were measured under the effects of different treatments. The results showed an increase of leaves content of (NPK) elements with increasing levels of spent mushroom compost in the growing medium. Also, an increase in the tubers contents of starch, K and dry matter were observed while a decrease in tubers ash content was registered.